ANALISIS PENGARUH STRUKTUR MODAL, DAN PROFITABILITAS TERHADAP EARNING PER SHARE (Studi Pada 14 Perusahaan Manufaktur Sektor Industri Food and Beverage di Indonesia yang Terdaftar dalam Bursa Efek Indonesia Periode 2014- 2016) - Erni Damayanti; Rodhiyah Rodhiyah (Universitas Diponegoro, 2018)
Earnings per share show the ability of the company to provide return to the owner of the company. This study aims to analyze the effect of Debt to Equity Ratio (DER), Debt to Assets Ratio (DAR), Return On Assets (ROA) and Return on Equity (ROE) to earnings per share. The population of 15 manufacturing companies engaged in the Food and Beverage industry sector listed on the Indonesia Stock Exchange 2014-2016. The data used are primary data from Financial Statement. Total samples meeting the criteria were 39 samples. The analysis technique used is linear regression analysis with SPSS program. Partially Debt to Equity Ratio (DER) and Debt to Assets Ratio (DAR) have no significant effect to earnings per share, while Return On Assets (ROA) and Return on Equity (ROE) have a significant positive effect to earnings per share. Simultaneously, Debt to Equity Ratio (DER), Debt to Assets Ratio (DAR), Return On Assets (ROA) and Return on Equity (ROE) have significant effect to earnings per share.